Positive energy schools with cool materials and passive strategies: scenarios and perspectives for the Brazilian context - Correia, Camila Machado de Azevedo (2024)
Tese (doutorado)—Universidade de Brasília, Faculdade de Arquitetura e Urbanismo, Programa de Pós-Graduação em Arquitetura e Urbanismo, 2024.